2016
DOI: 10.1038/srep37273
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin upregulates αB-Crystallin to protect the myocardium against heat stress in broiler chickens

Abstract: We established in vivo and in vitro models to investigate the role of αB-Crystallin (CryAB) and assess the ability of aspirin (ASA) to protect the myocardium during prolonged heat stress. Thirty-day-old chickens were divided into three groups (n = 90): heat stress (HS, 40±1 °C); ASA(−)HS(+), 1 mg/kg ASA orally 2 h before heat stress; and ASA(+)HS(−), pretreated with aspirin, no heat stress (25 °C). Hearts were excised after 0, 1, 2, 3, 5, 7, 10, 15 and 24 h. Heat stress increased body temperature, though the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…The enhanced expression and secretion of HspB5 have been observed in different cell types, including endothelial cells [ 45 ]. Therefore, results obtained in the present study using CM to reduce amylin toxicity might be explained by the presence of HspB5 in the CM ( Figure 3 ), and our data are in agreement with literature data showing how an increased production of HspBs, and specifically HspB5, prevents cell death [ 46 , 47 , 48 ]. In particular, part of the protective effects observed in SH-SY5Y cells may depend on the ability of HspB5 in counteracting the aggregation of amyloid peptides [ 49 , 50 ], and thus, the formation of more toxic species such as the oligomers [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The enhanced expression and secretion of HspB5 have been observed in different cell types, including endothelial cells [ 45 ]. Therefore, results obtained in the present study using CM to reduce amylin toxicity might be explained by the presence of HspB5 in the CM ( Figure 3 ), and our data are in agreement with literature data showing how an increased production of HspBs, and specifically HspB5, prevents cell death [ 46 , 47 , 48 ]. In particular, part of the protective effects observed in SH-SY5Y cells may depend on the ability of HspB5 in counteracting the aggregation of amyloid peptides [ 49 , 50 ], and thus, the formation of more toxic species such as the oligomers [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the ability of HSPs to scavenge ROS and maintain a redox balance is well-recognized (Tian et al, 2016;Venkatakrishnan, Cardounel, Zweier, Kuppusamy, & Llangovan, 2006). Our previous studies have reported that pretreatment with aspirin or coenzyme Q10 can induce HSP expression, consequently enhancing the heat resistance of the heart tissue and cardiomyocytes (Tang et al, 2014;Tang et al, 2016;Xu, Tang, Song, Yin, & Wu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress is a major environmental issue exacerbated by global warming that influences human health, affects animal growth and development, decreasing livestock production and causing sudden death in extreme cases (Crandall and Wilson 2014;Niu et al 2009). Heat stress can also damage important organs like the heart (Cui and Sinoway 2014;Tang et al 2016b) and induce tissue damage associated with sudden death. Heat stress can also destroy the integrity of the tight junctions of myocardial cells, and injure the structure and function of cell membranes (Aitken-Buck and Lamberts 2017; Crandall and Wilson 2014;Cui and Sinoway 2014).…”
Section: Introductionmentioning
confidence: 99%